1998
DOI: 10.1074/jbc.273.47.30863
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of a Novel pH-sensitive Two Pore Domain K+ Channel from Human Kidney

Abstract: A complementary DNA encoding a novel K ؉ channel, called TASK-2, was isolated from human kidney and its gene was mapped to chromosome 6p21. TASK-2 has a low sequence similarity to other two pore domain K ؉ channels, such as TWIK-1, TREK-1, TASK-1, and TRAAK (18 -22% of amino acid identity), but a similar topology consisting of four potential membrane-spanning domains. In transfected cells, TASK-2 produces noninactivating, outwardly rectifying K ؉ currents with activation potential thresholds that closely follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
332
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 340 publications
(351 citation statements)
references
References 43 publications
12
332
4
Order By: Relevance
“…Recently, the importance of TASK2 in NaHCO 3 absorption in the proximal tubule has been established, and TASK2-deficient animals have a metabolic acidosis and hypotension (3). TASK2 currents are noninactivating and show no voltage dependence (2). It has also been shown that intracellular sodium causes a concentration-and voltagedependent block of TASK2 channels such that TASK2 demonstrates a weak inward rectification (4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the importance of TASK2 in NaHCO 3 absorption in the proximal tubule has been established, and TASK2-deficient animals have a metabolic acidosis and hypotension (3). TASK2 currents are noninactivating and show no voltage dependence (2). It has also been shown that intracellular sodium causes a concentration-and voltagedependent block of TASK2 channels such that TASK2 demonstrates a weak inward rectification (4).…”
mentioning
confidence: 99%
“…It has also been shown that intracellular sodium causes a concentration-and voltagedependent block of TASK2 channels such that TASK2 demonstrates a weak inward rectification (4). TASK2 currents are inhibited by lidocaine and bupivacaine and potentiated by halothane and chloroform (2). TASK2 is also sensitive to changes in the osmotic potential of the external medium and participates in cell volume regulation (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because no or only weak expression of Task2 has been found in the brain (22), this channel has not been considered for cen-tral chemoreception. Task2 has been described as an epithelial channel, abundant in kidney, salivary glands, and the colon.…”
mentioning
confidence: 99%
“…Increased cytosolic cAMP inhibits TREK -1 and TREK -2 but not TRAAK (Reyes et al 1998 ;Patel et al 1998 ;. We used forskolin, a direct activator of adenylate cyclase, to increase cAMP in the bladder cells.…”
Section: Effect Of Forskolin On Sac -And Aa -Induced Currentsmentioning
confidence: 99%